Technical note: Device for measuring respiration rate of cattle under field conditions - Milan, H. F. M.; Maia, A. S. C. [UNESP]; Gebremedhin, K. G. (Oxford Univ Press Inc, 2016)
Respiration rate (RR) is 1 of the physiological responses used to gauge the level of heat stress in cattle. Respiration rate is usually measured by counting chest movement of the animal. This procedure has some disadvantages including that the person who is doing the counting must be trained to ensure accurate results, the animals must be preconditioned to the presence of the observer, and the presences of the observer may influence the behavior and activity of the animals or their position in the pen. In this study, a device that continuously records RR without restraining the animal was developed. The device is lightweight, cheap, easy to install, and more importantly, does not interfere with the activities of the animal. The device is mounted in a halter and is placed around the neck of the subject. The device measures air temperature near the nostrils of the animal and RR is calculated as the number of oscillations of the temperature. The RR measured by the device were compared against RR observed by counting the flank movement (for 60 s, repeated every 10 min) of 5 Nellore cattle, 1 animal per d, and the results show no statistical difference (P = 0.45) between the 2 methods. This demonstrates that this device can be used to continuously measure RR of cattle under field conditions.
Keywords: cattle; continuous measurement; measuring device; respiration rate